Church support networks of African Americans: The impact of gender and religious involvement. Issue 5 (27th February 2019) - Nguyen, Ann W.; Taylor, Robert Joseph; Chatters, Linda M.; Hope, Meredith O.
Abstract: We examined the sociodemographic and religious involvement correlates of church support networks in a nationally representative sample of African Americans across the adult life span. Data from the National Survey of American Life was used for analysis. Ordinary least squares regression was conducted to identify correlates of frequency of contact, subjective closeness, provision and receipt of overall support, receipt of emotional support, and negative interactions with church members. We also investigated differences in church support networks separately for men and women. Religious involvement was positively associated with church support network indicators (i.e., frequency of contact). Church support network indicators also varied by age, gender, education, family income, marital status, and region. The findings indicate that for many African Americans, church members are an integral component of their support networks and underscore the importance of social integration in church networks for social support exchanges. Moreover, these church support network characteristics are patterned by sociodemographic characteristics.